APPLICATION OF GEOGEBRA APPLICATION TO STUDENTS' GEOMETRIC THINKING SKILLS AND LEARNING INTERESTS THROUGH A PROJECT-BASED LEARNING MODEL - Hidayati, Penti; Hamidah, Hamidah; Ayuningtyas, Vidya; Kusuma, Jaka Wijaya (Yayasan Education and Social Center, 2024)
Mathematics is very important for understanding and problems of daily life, one of which is the branch of mathematics that studies the shape of surrounding objects is geometry. In fact, students' interest in learning and geometric thinking skills are still relatively low. The purpose of this study is to find out whether students' geometric thinking skills and students' learning interests given learning with the project based learning (PjBL) model assisted by the Geogebra application are better than those given by conventional learning. The design of this study is true experimental design the pretest posttest control group design. The sample was selected using random sampling technique. Data collection techniques by providing geometric thinking ability test questions and mathematical learning interest questionnaires to students. The data obtained was analyzed using the mean difference test. From the results of the posttest data analysis of the experimental and control classes, a sig value of 0.001 < 0.05 was obtained, which means that the geometric thinking ability of students who were given learning with the project based learning (PjBL) model assisted by the Geogebra application was better than that given by conventional learning. Furthermore, it is known that the average results of the learning interest questionnaire for students in the experimental class are 76.56 and in the control class is 59.94. So it can be concluded that the learning interest of students who use the project-based learning (PjBL) learning model assisted by the Geogebra application is better than students who use the conventional learning model